Respuesta :
Answer:
a
Step-by-step explanation:
Given
y - 3 = [tex]\frac{1}{2}[/tex](x + 6)
Multiply through by 2 to clear the fraction
2y - 6 = x + 6 ( subtract 2y from both sides )
- 6 = x - 2y + 6 ( subtract 6 from both sides )
- 12 = x - 2y, that is
x - 2y = - 12 → a
bearing in mind that standard form for a linear equation means
• all coefficients must be integers, no fractions
• only the constant on the right-hand-side
• all variables on the left-hand-side, sorted
• "x" must not have a negative coefficient
[tex]\bf y-3=\cfrac{1}{2}(x+6)\implies y-3=\cfrac{1}{2}x+3\implies y=\cfrac{1}{2}x+6 \\\\\\ \stackrel{\textit{multiplying both sides by }\stackrel{LCD}{2}}{2(y)=2\left( \cfrac{1}{2}x+6 \right)}\implies 2y=x+12\implies -x+2y=12 \\\\[-0.35em] ~\dotfill\\\\ ~\hfill x-2y=-12~\hfill[/tex]